Optimizing saffron cormlet production through substrate composition nutrient concentration and irrigation management in soilless cultivation - Elham Naseri; Neda Dalir; Ali Mokhtassi-Bidgoli; Mohammad-Taghi Ebadi; Rasoul Rahnemaie (Scientific Reports)
Abstract A two-year study has been conducted to optimize saffron cormlet production in a soilless cultivation system. Variations in the concentration of phosphate, boron, and irrigation events were assessed in the first year. Subsequently, after optimizing the substrate composition, the effects of nutrient solution volume and the concentration of nitrate, iron, and boron were investigated on the yield and weight of cormlets and leaves, photosynthetic activities, and productivity of nutrient solutions in the second year. Irrigation events in the first year significantly influenced cormlet growth, while phosphate and boron had no substantial effects. Moisture characteristics indicated an optimal substrate composition of 15% cocopeat, 15% cocochips, and 70% perlite. In the second year, increasing nutrient solution volume (225 ml/pot/week) and nitrate concentration up to 9800 µM significantly increased the weight of the leaf, total photosynthesis rate, and large-sized cormlets (> 8 g) to nearly 50% of total cormlets. Conversely, increasing iron concentration notably decreased the weight of total and large-sized cormlets. Boron concentration again showed no significant effect on the parameters. The highest nutrient solution productivity was achieved with a 150 (ml/pot/week) nutrient solution containing 9800 µM nitrogen and 25 µM iron. These findings underscore the importance of effective irrigation and nutrition management in enhancing the quantity and quality of cormlet production, potentially boosting perennial saffron yield in the following years.